Weed Management in Wheat (Triticum aestivum L.): A Review - Dhirendra Pratap Singh,; Abhishek Govind Rao, (Public Health, 2026)
Wheat (Triticum aestivum L.) is one of the most important cereal crops globally and a major contributor to food security. However, weed infestation is a serious constraint in wheat production, causing significant yield and economic losses. Weeds compete with crop plants for nutrients, moisture, light, and space, leading to reduced productivity. Yield losses due to weeds in wheat may reach up to 24% or more depending on weed density and environmental conditions . This review focuses on major weed flora, crop–weed competition, critical periods of weed control, and various weed management strategies including cultural, mechanical, chemical, and integrated approaches. Emphasis is placed on sustainable weed management practices to enhance wheat productivity and environmental safety. Weeds are among the most persistent biotic constraints in wheat production, causing yield losses of 20–40% if unmanaged. Conventional reliance on herbicides has led to resistance in major weed species such as Phalaris minor, necessitating integrated approaches. This review synthesizes cultural, mechanical, chemical, and biological methods, emphasizing Integrated Weed Management (IWM) as a sustainable pathway. Challenges such as herbicide resistance, environmental concerns, and climate variability are discussed, with future directions highlighting precision agriculture, climate-smart practices, and ecological sustainability.